Uptake of iron from ferrous fumarate can be mediated by clathrin-dependent endocytosis in Hutu-80 cells - Tarczykowska, Agata; Malmberg, Per; Scheers, Nathalie (Frontiers in Molecular Biosciences, 2025)
Iron uptake in the intestinal epithelium is associated with transport of ferrous iron via the DMT1 transporter (SLC11a2; NRAMP2). In later years, uptake of iron from complex sources, such as nanoparticles, has been found to be mediated through endocytosis. Here we propose that iron from the simple salt ferrous fumarate, a common iron supplement, can be absorbed by clathrin-mediated endocytosis. We used siRNA to silence DMT1 transporter expression, pharmacological inhibition of endocytosis, and Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) to show that iron uptake from ferrous fumarate can be mediated by both transport via DMT1 and by clathrin-dependent endocytosis in Hutu-80 cells. Iron uptake (ferritin L) from ferrous fumarate (0.5 mM, 24 h) in DMT1 silenced cells was significantly decreased (60% ± 11%) in comparison to iron controls while a 1-h dose of ferrous fumarate (0.5 mM) significantly decreased ferritin L formation in the presence of the clathrin inhibitor chlorpromazine (61% ± 10%, in post-confluent cells and 37% ± 9% in non-confluent cells). A pilot showed a similar trend for Ferritin (H) levels (confluent cells) and for total cellular iron load (non-confluent cells). ToF-SIMS analysis revealed diminished membrane-associated iron load in endocytosis-inhibited ferrous fumarate treated cells. The reported results support a clathrin-mediated endocytosis mechanism for uptake of iron from ferrous fumarate in addition to iron uptake by DMT1. More studies are needed to understand what determines which uptake mechanism are employed and to which extent.